COVID-19 and diabetes mellitus patients - Pooyan Afzali Harsini; Ali Khani Jeihooni; Gholamreza Imani; Saeed Hamzehie; Hadis Safaei Moghadam; Fatemeh Alimohammadi Rozveh; Sahar Alizadegan (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2022)
Coronavirus (COVID-19) is an encapsulated virus with a self-positive-sense RNA genome that is proven to cause respiratory disease in humans. Coronaviruses (COVID-19) are a type of virus that infects the respiratory tract [1]. In most immunocompetent individuals, infection with human COVID-19 results in a moderate upper respiratory infection in the majority of cases. The outbreaks of the Severe  Acute Respiratory Syndrome (SARS) in Guangdong province, China, in 2003 and the Middle  East Respiratory Syndrome (MERS) in Middle Eastern countries a decade later were caused by two highly virulent COVID-19.